ANALISIS PENILAIAN SAHAM DENGAN METODE PRICE BOOK VALUE (PBV) GUNA KEPUTUSAN INVESTASI - Sri Sutrismi; Minarni, Eni; Sisdiyantoro, Krisan; Defilatifah (BEMJ : Business, Entrepreneurship, and Management Journal, 2023)
The research objective to know the value and position of stocks with the Price Book Value method as an investment decision by investors. The type of research used is quantitative descriptive with the object is a company in the High Dividend Index 20 in 2022 with a sample selection using a purposive sampling method. This research uses data analysis techniques in the form of the Price Book Value method. The results of the study show that there are eight stocks on the High Dividend Index 20 that are undervalued so the investment decision that can be taken is to buy these stock, the other three stocks are in a fairvalue condition so the recommended investment decision is to hold or wait and the other eight stocks are in overvalued condition so that the recommended investment decision is not to buy the stock.